2019
DOI: 10.7554/elife.48625
|View full text |Cite
|
Sign up to set email alerts
|

PUMILIO, but not RBMX, binding is required for regulation of genomic stability by noncoding RNA NORAD

Abstract: NORAD is a conserved long noncoding RNA (lncRNA) that is required for genome stability in mammals. NORAD acts as a negative regulator of PUMILIO (PUM) proteins in the cytoplasm, and we previously showed that loss of NORAD or PUM hyperactivity results in genome instability and premature aging in mice (Kopp et al., 2019). Recently, however, it was reported that NORAD regulates genome stability through an interaction with the RNA binding protein RBMX in the nucleus. Here, we addressed the contributions of NORAD:P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…NORAD was the first reported lncRNA maintaining genomic integrity via sequestering PUMILIO proteins (Lee et al, 2016). Munschauer et al (2018) proved that NORAD controls RNA-binding motif protein X-linked (RBMX) to assemble a ribonucleoprotein complex (NORAD-activated ribonucleoprotein complex 1), mainly including suppressors of genome instability topoisomerase 1, necessary for the assembly of topoisomerase complex NARC1 (Munschauer et al, 2018;Elguindy et al, 2019). Hu et al found that a p53-responsive lncRNA GUARDIN could maintain genomic integrity via the ceRNA mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…NORAD was the first reported lncRNA maintaining genomic integrity via sequestering PUMILIO proteins (Lee et al, 2016). Munschauer et al (2018) proved that NORAD controls RNA-binding motif protein X-linked (RBMX) to assemble a ribonucleoprotein complex (NORAD-activated ribonucleoprotein complex 1), mainly including suppressors of genome instability topoisomerase 1, necessary for the assembly of topoisomerase complex NARC1 (Munschauer et al, 2018;Elguindy et al, 2019). Hu et al found that a p53-responsive lncRNA GUARDIN could maintain genomic integrity via the ceRNA mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Norad-deficient mice undergo premature aging characterized by genomic instability and mitochondrial dysfunction ( Kopp et al, 2019 ). NORAD interacts with proteins such as PUMILIO and RBMX, which likely mediate its effects on genomic stability ( Munschauer et al, 2018 ; Elguindy et al, 2019 ). NORAD is highly expressed in ECs ( Michalik et al, 2014 ), which is required to limit endothelial senescence ( Bian et al, 2020 ).…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 99%
“…In mice, Norad deletion leads to genomic instability and mitochondrial dysfunction, with animals showing signs of premature aging; Norad null allele mice were found to have grey and thin fur, to show abnormal spine curvature characteristic of aging and to die earlier than wild-type mice (Kopp et al, 2019). While NORAD interacts with additional proteins (Munschauer et al, 2018;Tichon et al, 2018), a series of genetic experiments, including PUMILIO 2 overexpression in mice and NORAD expression in human cells deficient for NORAD, demonstrated that the aforementioned cellular and organismal phenotypes are linked to PUMILIO hyperactivity (Elguindy et al, 2019;Kopp et al, 2019;Lee et al, 2016;Tichon et al, 2016). This example demonstrates the importance of clustered RNA motifs/ elements in establishing functional lncRNA-protein interactions that play key roles in cell biology and normal physiology.…”
Section: Unbiased Identification Of Lncrna Subcellular Localization Motifsmentioning
confidence: 99%